Development of Learning Media Based on Kinemaster Pro Application in History Subjects - Guritno, Galih; Susanti, L.R. Retno (JURNAL DIMENSI PENDIDIKAN DAN PEMBELAJARAN, 2025)
This study aims to develop learning media based on kinemaster pro applications that are effective and efficient. This research is a type of research that uses the Alessi & Trollip development model. The purpose of this research is to develop learning media based on kinemaster pro applications that are valid and have an effective impact on history learning. The validity of the developed product is based on the results of validation conducted by several experts, namely media experts, material experts and learning design experts. The results of the validation of media experts are 3.93 with a valid category, material experts are 4.30 with a very valid category, and learning design with a value of 4.10 with a valid category. The effectiveness of the use of kinemaster pro application-based learning media can be seen in the learning outcomes of students who experienced an increase in learning outcomes by 43.61%. Furthermore, the N-gain is 0.78 which is included in the high category.